Effect of Medium pH and Ion Composition on Rat’s Isolated Hepatocyte Resistance to Hyperosmotic Stress - Sereda, T. P.; Lezhanin, S. N.; Koptelov, V. A.; Bondarenko, V. A. (Problems of Cryobiology and Cryomedicine, 2004)
The influence of the media with different cation and anion composition on rat’s isolated hepatocyte resistance to the hyperosmotic stress effect under different pH medium was studied. It was demonstrated that a damaging effect increased in K+ - Na+ - Li+ cation series; CH3COO- – Cl- – NO3- anion series. A pH decrease results in the augmentation of cell resistance in all observed media, a pH increase, in contrast, reduces the cell resistance to hyperosmotic stress. A temperature decrease levels the effects of both ion medium composition and alkaline pH.